Preparation and characterization of activated carbons from bamboo for adsorption studies on the removal of surfactants - Cheong, Wai Wan (2006)
Activated carbon is an adsorbent material which is widely used in pollutant removal and water purification processes. The main characteristics of activated carbon are its high surface area and high adsorption capacity with certain adsorbates. Various materials are reported can be used for the preparation of activated carbon, but the use of bamboo is rarely reported. In this study, four activated carbons were produced using bamboo cane. Three of the mentioned samples were activated chemically by using zinc chloride and concentrated hydrochloric acid as the activating agent. These samples were activated at 700 Â°C in nitrogen, carbon dioxide and water steam flow respectively. The fourth sample was physically activated in nitrogen flow at 700 Â°C. The prepared activated carbons were characterized by Fourier Transform Infrared Spectroscopy (FTIR), Thermogravimetry Analysis (TGA), Field Emission Scanning Electron Microscopy (FESEM), Energy Dispersive X-ray Spectroscopy (EDX) and nitrogen adsorption at 77 K. The moisture, carbon and ash content of the activated carbons were determined. The results showed that the activated carbon which was activated with zinc chloride in nitrogen flow is the best activated carbon. It has the highest surface area (1258.99 m2 g-1), the highest thermal stability and the highest adsorption capacity in the adsorption of non-ionic surfactant (Triton-X 100) and cationic surfactant (cetyl trimethyl ammonium bromide). Its adsorption capacity is higher for non-ionic surfactant compared to the cationic surfactant. All chemically-activated carbons exhibit ability to adsorb both surfactants but none of them had higher adsorption capacity than the commercial activated carbon. The activated carbon prepared from bamboo exhibits good surface characteristics and porosity properties. This indicates that bamboo has the potential to be a promising precursor for the production of activated carbon.